The effect of chitosan on growth and enzyme production in Ganoderma sp. in vitro and in vivo induction of plant defense response in oil palm - Ganeson, Menaka (2016)
The aim of this study was to evaluate the role of chitosan against Ganoderma pathogen of basal stem rot (BSR) disease under in vitro and in vivo conditions. Therefore, this study was conducted to investigate the effect of chitosan on (1) in vitro growth of Ganoderma sp. (2) production of lignin degrading enzymes (LDE) by Ganoderma sp. under in vitro cultivation system (3) disease severity and vegetative growth parameters on oil palm seedlings and (4) elicitation of plant defense response during the interaction between host-pathogen (oil palm-Ganoderma).